EFEK FITOHORMON PGPR TERHADAP PERTUMBUHAN TANAMAN JAGUNG (Zea mays) - Rahni, Nini Mila (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2012)
Plant Growth Promoting Rhizobacteria (PGPR) is hyper Rhizobakteri growingplants, which are groups of beneficial bacteria that actively colonize rizosfir. Plantgrowth hormones will meet their needs through the ability to get from rizosfir and filosfiras a result of the activity of PGPR in synthesising fitohormon. In the rhizosphere zone,the interaction of plants with PGPR has a very important role in maintaining soilbiological environment. One of the most common ways how PGPR increase nutrientcapture by plants that alter plant hormone levels. The purpose of this article shows theeffect of PGPR on plant growth fitohormon corn. Some of the genus Pseudomonas,Azotobacter, Bacillus, and Seratia identified as PGPR fitohormon producer that canimprove plant growth and yield of maize.